The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/molecules25184187
|View full text |Cite
|
Sign up to set email alerts
|

Sprouts and Needles of Norway Spruce (Picea abies (L.) Karst.) as Nordic Specialty—Consumer Acceptance, Stability of Nutrients, and Bioactivities during Storage

Abstract: Developing shoots, i.e., sprouts, and older needles of Norway spruce (Picea abies (L.) Karst.) have traditionally been used for medicinal purposes due to the high content of vitamins and antioxidants. Currently, sprouts are available as, for example, superfood and supplements. However, end-product quality and nutritive value may decline in the value-chain from raw material sourcing to processing and storage. We studied (1) impacts of different drying and extraction methods on nutritional composition and antiox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…Nevertheless, spruce sprouts offer a considerable business opportunity to the forest owners. An extensive review on the properties and the use of spruce sprouts has been recently published by Jyske et al 24 …”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, spruce sprouts offer a considerable business opportunity to the forest owners. An extensive review on the properties and the use of spruce sprouts has been recently published by Jyske et al 24 …”
Section: Introductionmentioning
confidence: 99%
“…Despite the rich chemistry of spruce sprouts, only a very few studies on their chemical composition have been reported to date 3,24–27 . A deeper understanding on the chemical makeup of spruce sprouts is required to evaluate their potential in different pharmaceutical, nutraceutical or technochemical applications.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations